Risk factors associated with resistance to HIV testing among transwomen in Brazil - Pinheiro Junior, F. M. L.; Kendall, C.; Martins, T. A.; Mota, R. M. S.; Macena, R. H. M.; Glick, J.; Kerr-Correa, F. [UNESP]; Kerr, L. (Routledge Journals, Taylor & Francis Ltd, 2016)
Transwomen are a high-risk population for HIV/AIDS worldwide. However, many transwomen do not test for HIV. This study aimed to identify factors associated with resistance to HIV testing among transwomen in Fortaleza/CE. A cross-sectional study was conducted between August and December 2008 with a sample of 304 transwomen recruited through respondent-driven sampling. Data analysis utilized Respondent-Driven Sampling Analysis Tool and SPSS 11.0. Univariate, bivariate, and multivariate analyses examined risk factors associated with resistance to HIV testing. Less than 18 years of age (OR=4.221; CI=2.419-7.364), sexual debut before 10 years of age (OR=6.760; CI=2.996-15.256), using illegal drugs during sex (OR=2.384; CI=1.310-4.339), experience of discrimination (OR=3.962; CI=1.540-10.195) and a belief that the test results were not confidential (OR=3.763; CI=2.118-6.688) are independently associated with resistance to testing. Intersectoral and targeted strategies aimed at encouraging the adoption of safer sexual behaviors and testing for HIV among transwomen are required.
Keywords: transwomen; HIV testing; resistance to test; HIV; AIDS; RDS; Brazil